Validation and normative data for a new dynamic instrument evaluating phonological processing skills in Italian first-grade students - Stefanelli, Silvia; Zaghini, Giorgia; Benassi, Erika; Vedovati, Francesca; Gragnaniello, Manuela; Savelli, Enrico; Stella, Giacomo (Frontiers in Psychology, 2026)
IntroductionPhonological processing skills are fundamental to children's language development and academic success. There is an increasing need for assessment tools that can reliably identify difficulties in these areas at the beginning of primary school. This concerns both children already diagnosed with Developmental Language Disorder (DLD) or Speech Sound Disorder (SSD) and those without a diagnosis who may still have a weak phonological system.AimThis study introduces a new tool for assessing phonological processing skills, called Parla-dino test, based on a dynamic assessment approach. The tool allows the observation of modifiability in the child's productions through graduated prompts, integrating quantitative performance with qualitative information.Materials and methodA sample of 105 Italian monolingual first-grade children was administered both the Parla-dino and Cossu's Phonological Processing Test (gold standard measure) to assess the convergent validity. Additionally, 15 first-grade children with DLD were compared to a matched group of 45 typically developing (TD) peers to examine discriminant validity.ResultsSignificant correlations were found between the Phonological Processing Test and both the static and dynamic scores on Parla-dino test (rs=0.74, p < 0.001; rs=0.78, p < 0.001). Children with DLD performed significantly worse than their TD peers on both static (U = 101, p < 0.001) and dynamic scores (U = 124, p < 0.001). Logistic regression showed that the dynamic score emerged as a significant predictor of group status (B = −0.128, SE = 0.037, Z = −3.39, p < 0.001), indicating that higher Parla-dino scores were associated with a lower likelihood of being classified in the DLD group. Specificity and sensitivity were calculated, and normative data for Italian first-grade students were provided.ConclusionsChildren with DLD who exhibit specific impairments in phonological processing showed limited modifiability in word production, even when facilitative cues were provided. This behavioral pattern may represent a potential marker of phonological processing difficulties and can contribute to a better understanding of DLD phenotypes. Accordingly, the Parla-dino test appears to be a valid and effective tool for identifying phonological vulnerability in Italian children at the beginning of primary school.